The Effects of Leadership Styles and the Communication Competency of Bank Managers on the Employee's Job Satisfaction: The Case of Turkish Banks - ERDİLEK KARABAY, MELİSA; ÇETİN, MÜNEVVER (ELSEVIER SCIENCE BV, 2012)
Various researches have involved with the leadership and its effects within the organizations in global literature. A number of theoretical models also deal with the leadership style, and the job satisfaction that focus on the several dimensions on employees' perceptions in an organization. Our study focuses on the notion that leadership styles and the communication competency of bank managers are the basic elements that affect the employees' job satisfaction in Turkish banks. The survey of this study is conducted on deposit banks in Turkey. The obtained data from the questionnaires are investigated through the SPSS statistical packaged software. Empirical findings reveal that interactive leadership style and communication competency have a stronger relationship with job satisfaction. However, transformational and individual oriented leadership don't have any clear influence on bank employees' job satisfaction.
Keywords: Leadership styles; Communication Competency and Job Satisfaction; Turkish Banks